Penguatan Kepastian Hukum Kewenangan Kejaksaan Sebagai Penyidik Dalam Tindak Pidana Korupsi Sidang Perkara Nomor Nomor 28/Puu-Xxi/2023 - Pradita Ajeng Sekar Arum (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Corruption cases in Indonesia still really need attention considering that the consequences can be detrimental to the state and society. Handling the eradication of corruption is then carried out by several state institutions which are given direct authority by law, one of which is through the Prosecutor's Office of the Republic of Indonesia. Legal certainty of authority is very necessary to create harmony between government institutions and avoid overlapping authority. Furthermore, in writing this article, we used an approach method, namely an empirical method with descriptive analytical research specifications. The formulation of the problem raised in this article is regarding legal certainty in strengthening the prosecutor's office as an investigator in criminal acts of corruption. Furthermore, the purpose of this article is to analyze legal certainty or the legal standing of the authority of the prosecutor's office as an investigator in criminal acts of corruption. The authority of the Prosecutor's Office is contained in Article 30 paragraph (1) letter d of Law 5 of 1991 concerning the Prosecutor's Office of the Republic of Indonesia which was later declared invalid by Law 16 of 2004 in conjunction with Law Number 11 of 2021 concerning Amendments to Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia. Then in Article 26 of Law no. 19 of 2019 Second amendment to UU No. 31 of 1999 concerning Corruption Crimes.